Association of pre-admission statin therapy and the inflammatory response in ST elevation myocardial infarction patients. (2nd January 2019) - Rozenbaum, Zach; Ravid, Dor; Margolis, Gilad; Khoury, Shafik; Kaufman, Natalia; Keren, Gad; Milwidsky, Assi; Shacham, Yacov
Abstract: Purpose: To demonstrate the possible association of statin therapy with C reactive protein (CRP) serial measurements in ST elevation myocardial infarction (STEMI) patients. Materials and methods: STEMI patients between 2008 and 2016 with available CRP data from admission were divided into two groups according to pre-admission statin therapy. A second CRP measurement was noted following primary coronary intervention (within 24 h from admission). The difference between the two measurements was designated ΔCRP. Results: The cohort consisted of 1134 patients with a median age of 61 (IQR52–70), 81% males. Patients on statins prior to admission (336/1134, 26%) were more likely to have CRP levels within normal range (≤5 mg/l) compared to patients without prior treatment, both at admission (75 vs. 24%, p = 0.004) and at 24 h (70 vs. 48%, p = 0.029). The prevalence of patients with pre-admission statin therapy decreased as ΔCRP increased ( p = 0.004; n = 301). The likelihood of ΔCRP to be above 5 mg/l in patients with pre-admission statin therapy was reduced after age and gender adjustments (OR 0.54, 95% CI 0.32–0.92, p = 0.023) and in multivariate (OR 0.57, 95% CI 0.33–0.99, p = 0.048) analysis. Conclusions: Pre-admission statin therapy is associated with a less robust inflammatory response in STEMI patients, highlighting statin's pathophysiological importance.